Craco, a Medieval Village. The “Re-invention of Places” Throughout new Forms of Anthropization and Museum Display - Rossella de Cadilhac; Maria Antonietta Catella (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2020)
In an age like the present one, marked by a growing sensitivity towards the issues of recovery and enhancement of minor historical centres, abandoned or in the process of depopulation, the case study of the medieval village of Craco is a practical example of the settlements in Lucania affected by this phenomenon. In 1963 a landslide undermined the survival of the village, so much to cause a progressive depopulation and transfer of all the inhabitants in the nearby village of Peschiera. A condition of geographic marginality, together with the state of decay of the village, now deprived of its original vocation and constant maintenance, has become an attractive note for an ever-increasing number of visitors. In 2013, the Scenographic Park of the ruins was established in Craco, which determined the securing of part of its buildings along a well-defined itinerary to secure part of its buildings along a welldefined itinerary. The precarious geological nature of the site makes the hypothesis of a complete recovery of the settlement unthinkable. Towards a valid proposal for conservation and enhancement of the village has been undertaken, whose results made it possible to formulate Guidelines, weighted between the two current antithetical visions: a positive one that considers possible the recovery, at least partial, of the built environment through new forms of anthropization, and a more cautious one looking to a museum display for tourists.